Simulation of a Collision between Passenger Car and Child Pedestrian - Schejbalová, Zuzana; Kvášová, Alžběta; Mičunek, Tomáš; Marek, Zdenč›k (Promet - Traffic&Transportation, 2012)
The Department of Forensic Experts in Transportation at the Faculty of Transportation Sciences performed a second set of dynamic passive safety tests of a passenger car (M1 category - Škoda Octavia II) in a child pedestrian collision. The initial and test conditions were similar to those of the first set of tests in September 2009 (Škoda Roomster). The deformations of the contact zones on the frontal vehicle surface were analyzed by a 3D scanning technology (3D handy scanner). Head, thorax and pelvic resultant acceleration, acceleration of knee joint in sagittal direction and contact force on the femoral structure of the dummy (P6 dummy, 1.17m; 22kg) were measured. The aim of these tests is to provide a detailed description of pedestrian kinematics and comparison of primary and secondary impact seriousness. KEY WORDS passenger car, child pedestrian, primary and secondary impact, dummy instrumentation, injury criteria, 3D scanning